2019
DOI: 10.1002/gj.3440
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a Mesoarchean suprasubduction zone mantle wedge in the Dharwar Craton, southern India: Evidence from petrology, geochemistry, zircon U–Pb geochronology, and Lu–Hf isotopes

Abstract: Petrological, geochemical, and zircon U–Pb geochronological features of Archean ultramafic–mafic complexes formed in subduction‐related settings provide significant insights into mantle source and geodynamic processes associated with subduction–accretion‐collision events in the early Earth. Here, we investigate a suite of serpentinized dunite, dunite, pyroxenite, and clinopyroxenite from an ultramafic complex along the collisional suture between the Western Dharwar Craton (WDC) and the Central Dharwar Craton (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 76 publications
(145 reference statements)
0
5
0
Order By: Relevance
“…Based on the geochemical and isotopic data, Santosh and Li (2018) suggested that extensive arc magmatism of similar age evidenced from the adjacent greenstone belts which mark the trace of ocean closure and correspond to multiple converge of microblocks at the end of Archean which are responsible for building the cratonic mosaic of the Dharwar. Based on the mineral chemistry, zircon U-Pb geochronology, rare earth element (REE), Lu-Hf isotopes, and whole rock geochemistry, Han et al (2019) investigated a suite of serpentinized dunite, dunite, pyroxenite, and clinopyroxenite from an ultramafic complex situated along the collisional suture between the western Dharwar Craton (WDC) and the Central Dharwar Craton (CDC). Zircon U-Pb age range from 2.9-2.6 Ga with an early Paleoproterozoic (ca.…”
Section: Greenstone Belts: Volcano-sedimentary Sequencesmentioning
confidence: 99%
“…Based on the geochemical and isotopic data, Santosh and Li (2018) suggested that extensive arc magmatism of similar age evidenced from the adjacent greenstone belts which mark the trace of ocean closure and correspond to multiple converge of microblocks at the end of Archean which are responsible for building the cratonic mosaic of the Dharwar. Based on the mineral chemistry, zircon U-Pb geochronology, rare earth element (REE), Lu-Hf isotopes, and whole rock geochemistry, Han et al (2019) investigated a suite of serpentinized dunite, dunite, pyroxenite, and clinopyroxenite from an ultramafic complex situated along the collisional suture between the western Dharwar Craton (WDC) and the Central Dharwar Craton (CDC). Zircon U-Pb age range from 2.9-2.6 Ga with an early Paleoproterozoic (ca.…”
Section: Greenstone Belts: Volcano-sedimentary Sequencesmentioning
confidence: 99%
“…The Chitradurga greenstone belt and associated shear zone marks the boundary between the WDC and the CDC and the Kolar–Kadiri greenstone belt divides the eastern edge of the CDC from the EDC. The 500‐km‐long north–south‐trending Closepet granite batholith is located within the CDC at the eastern margin of the Chitradurga greenstone belt (Chadwick et al, ; Chardon et al, , ; Han, Santosh, Ganguly, & Li, ; Jayananda, Peucat, et al, ; Jayananda, Tsutsumi, et al, ; Li et al, ). This batholith was formed by intrusion and crystallization of mantle‐derived mafic magma into pre‐existing TTG gneiss at 2.56–2.51 Ga causing fluid release and crustal anatexis (Moyen et al, ).…”
Section: Regional Geologymentioning
confidence: 99%
“…The contact between WDC and EDC is not sharp and a transition zone extending from Closepet granite to Chitradurga shear zone corresponds to the boundary between these two sectors of Dharwar Craton which has been demarcated as the Central Dharwar Province (CDP) or Central Dharwar Craton (CDC) based on magmatic and metamorphic age data Peucat et al, 2013). Based on U-Pb zircon ages and Nd isotope data, Peucat et al (2013) divided the Dharwar Craton into western (Chadwick et al, 2000;Chardon et al, 2008Chardon et al, , 2011Han, Santosh, Ganguly, & Li, 2019;Jayananda, Peucat, et al, 2013;Jayananda, Tsutsumi, et al, 2013;Li et al, 2018). This batholith was formed by intrusion and crystallization of mantle-derived mafic magma into pre-existing TTG gneiss at 2.56-2.51 Ga causing fluid release and crustal anatexis (Moyen et al, 2001).…”
mentioning
confidence: 99%
“…Other than those, the oldest Mesoarchaean-Palaeoproterozoic (c. 3000-2450 Ma) granulite-facies rocks in India are also reported from the Coorg block (Santosh et al 2015;Amaldev et al 2016), Karimnagar Granulite Belt (Santosh et al 2004;Prakash et al 2017) and the southern end of the Dharwar craton (Northern Granulite Terrane or Salem Block) that continues up to the Palghat-Cauvery Shear System (PCSS) within the Southern Granulite Terrane (SGT) (e.g. Rao et al 1996;Bhaskar Rao et al 2003;Braun & Kriegsman, 2003;Ghosh et al 2004;Clark et al 2009;Anderson et al 2012;Peucat et al 2013;Ram Mohan et al 2013;Santosh et al 2013;Brandt et al 2014;Samuel et al 2014;Raith et al 2016;Li et al 2018;George et al 2019;Han et al 2019;Talukdar et al 2019;Ratheesh-Kumar et al 2020). While the peak metamorphism of the Karimnagar Granulite Belt and Coorg block occurred in the Neoarchaean (c. 2600 Ma) and Mesoarchaean (c. 3000 Ma), respectively, the parts of the SGT (from Northern Granulite Terrane to PCSS) underwent peak metamorphism during the Archaean-Proterozoic boundary (c. 2700-2450 Ma).…”
Section: Introductionmentioning
confidence: 99%